First report of nematodes in the common lesser escuerzo Odontophrynus americanus (Duméril and Bibron, 1841) (Amphibia: Cycloramphidae) from Corrientes, Argentina - Gonzalez, Cynthya Elizabeth (2009)
The common lesser escuerzo, Odontophrynus americanus, from Corrientes, Argentina, was found to harbor 3 species of Nematodes: Rhabdias elegans, Cosmocerca podicipinus, and Cosmocerca parva. Cosmocerca podicipinus was the most prevalent nematode species (22.7%), whereas C. parva had the highest mean intensity of infection (5.5 ± 2.12). These 3 nematode species are reported for the first time from O. americanus and members of the Cycloramphidae from Corrientes, Argentina.